Vegetative propagation of insulin (Cissus verticillata (L.) Nicolson & C.E. Jarvis) by cutting - C.T.A. CRUZ-SILVA; A.L.S. MARCON; L.H.P. NOBREGA (Universidade Estadual Paulista, 2015)
Propagation techniques may support handling, this way providing an alternative for producers of medicinal plants, thus avoiding indiscriminate collection. We aimed to evaluate the size of cuttings with and without leaves on the seedling production of insulin (Cissus verticillata (L.) Nicolson & C.E. Jarvis). The herbaceous apical cuttings were prepared with diagonal cut at the bottom and straight cut at the apex, with 5, 10 or 15 cm in length, kept with two whole leaves, two leaves cut in half or without leaves, being sterilized with sodium hypochlorite at 0.5% for 15 minutes. The cuttings were planted in plastic containers with 180 mL capacity with vermiculite as substrate and placed in greenhouse at the temperature of 22 ± 2° C. The experimental design was completely randomized and means were compared by Tukey's test at 5% probability. After 60 days, we found that the cutting of 5 cm with whole leaves and with leaves cut in half and the cutting of 10 cm with whole leaves had rates above 70% of rooting with the best means for number and length of roots. There was a high mortality rate for cuttings made without leaves. The callus and the percentage of live cuttings were not significant for the treatments. Therefore, 5 cm long cuttings with whole or half leaves and 10 cm long cuttings with whole leaves are the most suitable for the vegetative propagation of insulin.